Communicating science to students: Investigating professional botanic garden educators' talk during guided school visits. Issue 4 (30th January 2014) - Zhai, Junqing; Dillon, Justin
Abstract: Botanic gardens are popular destinations for school visits to learn about plant‐based science. However, little is known about teaching and learning in such settings, in particular about school visits guided by professional botanic garden educators (BGEs). The purpose of this study was to identify the pedagogical moves of the BGEs during guided school visits. More specifically, this study follows a qualitative research design, investigating six elementary school groups (7‐ to 11‐years old) guided by three BGEs. The guided visits were videotaped and the transcripts analyzed in order to find out the patterns of the BGE and student discourse. The findings from this study indicate that although BGE‐student dialogic interactions occasionally occurred, a non‐interactive/authoritative communicative approach was the more common practice of the BGEs when communicating science to students. However, the components of storytelling and the use of analogies identified have a great potential for enriching the explanatory talk of the BGEs. The results of this study suggest that the dynamics of discourse during guided school visits were shaped by both the BGEs and students through the shift of power during this discourse. © 2014 Wiley Periodicals, Inc. J Res Sci Teach 51: 407–429, 2014